Stress distribution and displacement of three different types of micro-implant assisted rapid maxillary expansion (MARME): a three-dimensional finite element study - C. B. André; J. Rino-Neto; W. Iared; B. P. M. Pasqua; F. D. Nascimento (SpringerOpen, 2021)
Abstract Background/objective Until 2010, adults underwent surgical treatment for maxillary expansion; however, with the advent of micro-implant-assisted rapid maxillary expansion (MARME), the availability of less invasive treatment options has increased. Nevertheless, individuals with severe transverse maxillary deficiency do not benefit from this therapy. This has aroused interest in creating a new device that allows the benefit of maxillary expansion for these individuals. The aim of this study was to evaluate the efficacy of three MARME models according to tension points, force distribution, and areas of concentration in the craniofacial complex when transverse forces are applied using finite element analysis. Materials and methods Digital modeling of the three MARME models was performed. Model A comprised five components: one body screw expander and four adjustable arms with rings for mini-implant insertion. These arms have an individualized height adjustment that allows MARME positioning according to the patient's palatal anatomy, thereby preventing body screw expander collision with the lateral mucosa in severe cases of maxillary deficiency. Model B was a maxillary expander with screw rings joined to the body, and model C was similar to model B, except that model C had open rings for the insertion of the mini-implants. Through the MEF (Ansys software), the stresses, distribution, and area of concentration of the stresses were evaluated when transverse forces of 7.85 N were applied. Results The three models maintained the following pattern: model C presented weak stress peaks with limited distribution and lower concentration area, model B obtained median stress peaks with better distribution when compared to that of model C, and model A showed better stress distribution and larger concentration area. In model A, tensions were located in the lateral lamina of the pterygoid process, which is an important site for maxillary expansion. The limitation of the present study was that it did not include the periodontal tissues and muscles in the finite element method evaluation. Conclusions Model A showed the best stress distribution conditions. In cases of severe atresia, model A seems to be an excellent option.